The Compilation of Village Map in Community Service Activities in Blumbungan Village, Larangan District, Pamekasan Regency - Nasrullah, Nasrullah; Rizal, Rizal; Nuzammil, Muzammil; Muharrom, Wahedi; Umam, Khairul (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2023)
Blumbungan Village is one of the sub-districts/village which has the largest area in Pamekasan Regency. So that information is needed in the form of administrative maps and public facilities that can be used to support the village government in managing their household. The purpose of this community service is village mapping as a basis for regional development in the Blumbungan Village area, Pamekasan Regency. The methods used include surveys, preparation stages, map making processes, temporary print outs, permanent print outs, and map handover. Community service activities in Blumbungan Village produced a village map containing geospatial information that can be found in the area. The information is in the form of administrative area boundaries, transportation networks/infrastructure, waters, facilities and infrastructure. The image displayed on the village map provides an overview of the land cover in Blumbungan Village. Land use at certain points has the possibility of land conversion, so that it becomes a new land use. Therefore, it is necessary to update the presentation of the map from time to time to adapt to the current conditions in Blumbungan Village. In development planning, maps are used as material for regional analysis by taking into account land cover. In addition, the level of settlement density can be used as material for analysis of development planning in the form of public facilities that can be utilized by the community. Blumbungan Village is dominated by settlements, only a few green open spaces are available. Diversion of land for green open space can be planned by utilizing maps.